2017
DOI: 10.1139/cjc-2016-0344
|View full text |Cite
|
Sign up to set email alerts
|

Rotational barriers in five related amides

Abstract: 30Interest in the low carbonyl infrared frequency of 2-hydroxy-N,N-bis(2-hydroxyethyl)acetamide 31 (2) initially prompted our interest in the amide rotational barrier of this molecule and four related 32 amides which present a variety of hydrogen-bonding possibilities. In the course of this study, a 33 previously incorrect structural assignment was established as N, N-bis[2-(acetyloxy)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…All values of the Gibbs free energy were in the same range of 61.4 to 66.2 kJ/mol and in agreement with previously published values for carbamates . The obtained Gibbs free energies for the rotational barriers of all studied carbamates are approximately 10 kJ/mol smaller than the barriers for structurally similar acetamides …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…All values of the Gibbs free energy were in the same range of 61.4 to 66.2 kJ/mol and in agreement with previously published values for carbamates . The obtained Gibbs free energies for the rotational barriers of all studied carbamates are approximately 10 kJ/mol smaller than the barriers for structurally similar acetamides …”
Section: Resultssupporting
confidence: 91%
“…In a previous study, Greenberg compared five structurally related amides with or without the ability for intramolecular hydrogen bonding. By DNMR studies and the coalescence method, it was found that hydrogen bonding contributed only little to the barriers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations